A case report of TBL1XR1-RARB positive pediatric acute promyelocytic leukemia and literature review - Du, Chunyan; Liu, Fu; Huang, Linlin; Zeng, Ruxue; Fan, Jiamei; Hu, Tao (Frontiers in Oncology, 2025)
BackgroundAcute promyelocytic leukemia (APL) is classically driven by the PML-RARA fusion oncogene and characterized by a maturation arrest of myeloid precursors. Variant APL (vAPL) with alternative RARA rearrangements presents diagnostic and therapeutic challenges.MethodsWe report a novel case of TBL1XR1-RARB-positive vAPL and conducted a comprehensive literature review to synthesize clinical and molecular data from all previously reported cases of this rare entity.ResultsOur patient presented with neutrophilic leukocytosis (15.44×10⁹/L) and an absence of peripheral promyelocytes, exhibiting fever as the sole symptom, an atypical CD45⁻/CD117⁻ immunophenotype, and a concurrent KRAS p.G12D mutation. Despite an initial response to ATRA/ATO therapy, relapse occurred during maintenance. Our literature review of all reported cases revealed key patterns: a predominant pediatric occurrence (median age 2.7 years), frequent ATRA/ATO resistance (55% response rate), and a high risk of relapse (44%).ConclusionThis study underscores the molecular heterogeneity and distinct clinical course of TBL1XR1-RARB-positive vAPL. It highlights significant therapeutic challenges, including a high rate of primary resistance and relapse, and provides critical guidance for the management of this rare but clinically significant disease.